Software de simulación del examen complexivo para evaluar los conocimientos de los estudiantes de la Facultad de Administración Finanzas e informática de la UTB - Morante Jiménez, Jorge Alberto (2020)
In accordance with the provisions of the Organic Law of Higher Education "LOES", final year students must be evaluated prior to obtaining the respective title, so the System Engineering career together with the degree unit, offer options of qualification to the students of which one of them is the Complexive exam. For this degree option, the Technical University of Babahoyo does not have a web application system that allows optimal management of complex exams. It should be noted that the handling of manual information and the paper record entails several problems such as: disorganization, improper handling and possible loss of sensitive documentation, for which a web application was offered that allows to optimally carry out the corresponding management to be used. in complex exams also considering the requirements related to this process. The application in which it is developed through the use of Open Source such as: SQLPostgres, Wampserver, NotePad ++, PHP. Additionally, an MVC software architecture pattern (Model, View, Controller) was used, which separates the data and business logic of an application from the user interface and the model in charge of managing events and communications, allowing ease of maintenance, code reuse and separation of concepts. The final result was a web application that is easy to use and administer, which covers the processes involved and used in the complex exam, from the creation, follow-up and approval of the same to the generation of the exam automatically, thus allowing them to be performed in an automatic way. efficient each of the tasks of the Degree Unit. In addition, the option of an exam simulator is offered, which will be available from the website of the degree unit.